The Effects of Hyperbaric Oxygen with 1.5 ATA and 2.4 ATA Pressures toward Improvement Maximum Aerobic Capacity (VO2 Max) and the Anaerobic endurance on Man-Basketbal Players - Lalu Moh Yudha Isnaini; Soegiyanto Soegiyanto; Sugiharto Sugiharto; Sulaiman Sulaiman (AIBPM Publisher, 2019)
The purpose of this research is generally to gain implication of hyperbaric oxygen with 1.5 ATA and 2.4 ATA pressures toward maximum aerobic capacity improvement (VO2 Max) and the anaerobic endurance. This experimental research uses randomized controlled group pretest and posttest design. The tests were bleep or MFT test to measure the maximum aerobic capacity (VO2 Max) and RAST test to measure the anaerobic endurance. The conclusion of this research is hyperbaric with 1.5 ATA and 2.4 ATA significantly influenced the maximum aerobic capacity improvement (VO2 Max) and anaerobic endurance. Hyperbaric oxygen with 1.5 and 2.4 ATA did not have any differences in improving the maximum aerobic capacity (VO2 Max) and the anaerobic endurance.